Customer Relationship Management (CRM) Analysis in Customer Retention - Rudy Haryanto; Yovita Yulia M. Zai; Ardi Azhar Nampira; Ana Yuliana; Eva Desembrianita (Dinasti International Journal of Education Management And Social Science, 2025)
The purpose of this study is to analyze Customer Relationship Management (CRM) in customer retention. This research approach collects data through a literature study, which involves reading literature from various sources including books, reports, articles, and journals through qualitative and deductive approaches. The findings of this study are that Customer Relationship Management (CRM) is an important strategy in increasing customer retention. By utilizing precise segmentation, personalized service, consistent multi-channel interactions, and real-time satisfaction monitoring, CRM helps companies build stronger and more sustainable relationships with customers. Systematic CRM implementation has been proven to increase loyalty, satisfaction, and operational efficiency, as well as reduce marketing costs. Case studies of global companies such as Amazon and Starbucks demonstrate the success of this strategy in encouraging repeat purchases and strengthening emotional bonds with customers. However, CRM implementation also faces challenges such as lack of system integration, poor data quality, internal resistance, limited technical human resource capabilities, and high implementation costs.